Modelling Buffer-Overflow in 6LoWPAN-Based Resource-Constraint IoT-Healthcare Network - Verma, Himanshu; Chauhan, Naveen; Awasthi, Lalit Kumar (Wireless personal communications, 2023)
Healthcare is one of the prominent domains that can benefit from numerous revolutionary features of the Internet of Things. Proactive, personalized, and connected healthcare is promised with the amalgamation of IoT in the healthcare sector. Recent advancements in the Wireless Sensor Network and IPv6 over Low-Power Wireless Personal Area Networks provide hopes for implementing the ‘ Internet of Healthcare Things ’. Such an application demands real-time, time-critical, instantaneous, zero loss of information at a higher data rate from resource-constraint medical sensing devices. Such requirements create new and never-foreseen challenges in front of researchers. Sincerely addressing congestion for the 6LoWPAN-based resource-limited IoHT network is a severe challenge. This paper discusses the situations of congestion occurrence, the steps required for mitigation, and the factors affecting congestion. As identified, buffer overflow is a discernible cause that leads to congestion and further loss of information. An analytical model that estimates the probability of packet loss incurred due to buffer overflow in patient-centric resource-constraint IoT-healthcare networks has been presented. The buffer-loss probability, the number of packets lost, and the total number of packets received at the local sink are calculated in the results.